2022
DOI: 10.1002/adma.202203744
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the Micropore Confinement Effect of Carbonaceous Electrodes for Promoting Zn‐Ion Storage Capability

Abstract: Zinc‐ion capacitors (ZICs) are promising technology for large‐scale energy storage by integrating the attributes of supercapacitors and zinc‐ion batteries. Unfortunately, the insufficient Zn2+‐storage active sites of carbonaceous cathode materials and the mismatch of pore sizes with charge carriers lead to unsatisfactory Zn2+ storage capability. Herein, new insights for boosting Zn2+ storage capability of activated nitrogen‐doped hierarchical porous carbon materials (ANHPC‐x) are reported by effectively elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 59 publications
2
57
0
Order By: Relevance
“…However, H + (aq) is usually presented in aqueous electrolyte due to the hydrolysis of Zn 2+ , which will interfere with the understanding of the energy storage mechanism because H + (aq) can easily contribute to pseudocapacitance by reversibly reacting with the functional groups on carbon. This phenomenon has been proved by several pioneer works that some oxygenated carbons exhibit Zn 2+ and H + costorage behavior in aqueous Zn-ion capacitors. ,, Specifically, Xu et al showed that the reduced graphene oxide (heat treatment at 200 °C) performed 245 F g –1 in the aqueous electrolyte, while only 146 F g –1 in the organic electrolyte in which H + (aq) is not present. Therefore, for an in-depth understanding of the effect of self-doping defects on electrochemical performance, we assembled the Zn-ion capacitors in not only aqueous electrolyte but also organic (acetonitrile) electrolyte (Figure ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, H + (aq) is usually presented in aqueous electrolyte due to the hydrolysis of Zn 2+ , which will interfere with the understanding of the energy storage mechanism because H + (aq) can easily contribute to pseudocapacitance by reversibly reacting with the functional groups on carbon. This phenomenon has been proved by several pioneer works that some oxygenated carbons exhibit Zn 2+ and H + costorage behavior in aqueous Zn-ion capacitors. ,, Specifically, Xu et al showed that the reduced graphene oxide (heat treatment at 200 °C) performed 245 F g –1 in the aqueous electrolyte, while only 146 F g –1 in the organic electrolyte in which H + (aq) is not present. Therefore, for an in-depth understanding of the effect of self-doping defects on electrochemical performance, we assembled the Zn-ion capacitors in not only aqueous electrolyte but also organic (acetonitrile) electrolyte (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…Defect engineering of carbon materials has been widely investigated for electrocatalytic reactions and/or energy storage. The foreign-doping defects (e.g., heteroatoms and functional groups) not only serve as the active sites but also endow the carbon materials with some novel functions such as high activity and good surface wettability. For example, Alshareef and Zhao proposed that oxygen-bearing functional groups possessed a reversible pseudocapacitive behavior by reacting with H + and Zn 2+ to enhance the energy storage ability of porous carbon for aqueous Zn-ion capacitors. Lu revealed that nitrogen-bearing functional groups could generate pseudocapacitance by reducing the energy barrier of C–O–Zn bonding.…”
Section: Introductionmentioning
confidence: 99%
“…3c). 42 The TEM and derived mapping images of GCNF certify that C, N, and O elements are uniformly distributed throughout GCNF, illustrating that the nitrogen heteroatom is in situ integrated into GCNF due to the employment of nitrogenous PAN (Fig. 3d).…”
Section: Fabrication and Characterization Of Gcnfmentioning
confidence: 75%
“…These results were used to determine the ratio of diffusion-controlled and non-diffusion-controlled contributions to the overall cycling capacity. [33,34] Based on calculations of pseudocapacitive contributions in the Supporting Information, the fitted slope b-values are 0.82, 0.85, 0.84, and 0.87, revealing a synergistic charge storage based on diffusion-controlled and capacitive processes (Figure 4g). The detailed pseudocapacitance ratio was 52.7 % at a scan rate of 3.0 mV s À 1 (Figure 4h).…”
Section: Resultsmentioning
confidence: 99%